Penerapan Metode Disiplin Dalam Penggunaan RPP Guru Mengajar di SD Negeri 034 Kijang Rejo - Alirman, Alirman (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
School is a place where the process of teaching and learning formally, so that the learning process is running and get results in accordance with the expected learning objectives, then many things that mempengaruinya include the basic plan of learning (RPP). Through the school action research is qualitatively analyzed, the result of the research shows that by applying the discipline method in preparing the RPP, applying it and also requesting to be supervised and evaluated make the application of RPP in school by the teacher is increasing. Keywords: Discipline method, use of RPP